2024
DOI: 10.3389/fpls.2023.1304327
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the transitory and local effect of zebularine on development and on proteome dynamics of Salix purpurea

Andrea Pagano,
Carolina Gomes,
Evy Timmerman
et al.

Abstract: IntroductionDNA methylation plays major roles in the epigenetic regulation of gene expression, transposon and transcriptional silencing, and DNA repair, with implications in developmental processes and phenotypic plasticity. Relevantly for woody species, DNA methylation constitutes a regulative layer in cell wall dynamics associated with xylogenesis. The use of methyltransferase and/or demethylase inhibitors has been proven informative to shed light on the methylome dynamics behind the regulation of these proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 59 publications
(69 reference statements)
0
0
0
Order By: Relevance
“…At high concentrations (100 μM), the plantlets did not survive, while no significant visual differences were observed at lower concentrations (15 μM) between the control and treated plantlets. Consistent with the findings of Pagano et al (2024), treatment with 50 μM zebularine resulted in significant developmental differences compared to the control samples, such as the absence of root development in the treated samples (Figure 1A). However, during the recovery period, in the absence of zebularine, the plantlets began to develop roots.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…At high concentrations (100 μM), the plantlets did not survive, while no significant visual differences were observed at lower concentrations (15 μM) between the control and treated plantlets. Consistent with the findings of Pagano et al (2024), treatment with 50 μM zebularine resulted in significant developmental differences compared to the control samples, such as the absence of root development in the treated samples (Figure 1A). However, during the recovery period, in the absence of zebularine, the plantlets began to develop roots.…”
Section: Resultssupporting
confidence: 86%
“…In the current study, we collected buds from a single hybrid tree (genotype PSP33) from the experimental station of IGR Poznan to minimize somaclonal variation and cultured the buds in vitro using ½ MS medium supplement (Sigma-Aldrich) with 30 gÁL À1 sucrose (Duchefa) that was solidified using 8 gÁL À1 agar with vitamins (Micro-agar, Duchefa). Previously, we observed that 25 and 50 μM of zebularine modify DNA methylation (Pagano et al, 2024). In the current research, we re-optimized the zebularine concentration by applying 15, 25, 50, or 100 μM of zebularine as hypomethylation (demethylating) agent.…”
Section: Plant Material Zebularine Treatment and Growth Conditionsmentioning
confidence: 94%
See 1 more Smart Citation